Pengembangan Profesi Guru dalam Pengajaran Multikultural - Nasution, Pitriani; Abdillah, Addin (Pusdikra Publishing, 2024)
The development of a multicultural teaching profession is crucial in the context of Indonesia's diverse and multicultural education system. Multicultural education plays a significant role in enhancing teachers' ability to teach and influence students from various backgrounds. Teachers with multicultural competence can be more effective in teaching and influencing students, as well as creating inclusive and tolerant learning environments. To achieve this, teachers need to possess special competencies such as cultural awareness, multicultural knowledge, and diversity management skills. Teacher education should incorporate multicultural teaching components deeply, along with continuous professional training and development. Thus, teachers can create learning environments that value differences and promote active participation from all students, regardless of their backgrounds.